Non-Isothermal Degradation Kinetics of CaCO3 from Different Origin - Velyana Georgieva; Lyubomir Vlaev; Kalinka Gyurova (Journal of Chemistry)
Thermogravimetric studies on two varieties of calcium carbonate, namely, analytical reagent-grade and in situ product from thermal degradation of calcium oxalate monohydrate, were carried out at four rates of linear increase of the temperature. The kinetics and mechanism of their solid-state thermal decomposition reaction were evaluated from the TG data using four calculation procedures and isoconversion method, as well as 27 mechanism functions. The comparison of the results obtained with these calculation procedures showed that they strongly depend on the selection of proper mechanism function for the process. Therefore, it is very important to determine the most probable mechanism function. In this respect the isoconversion calculation procedure turned out to be more appropriate. In the present work, the values of apparent activation energy E, preexponential factor A in Arrhenius equation, as well as the changes of entropy , enthalpy , and free Gibbs energy for the formation of the activated complex from the reagent are calculated. All calculations were performed using programs compiled by ourselves.